Analisis Kinerja Pegawai Terdampak Lingkungan Kerja Non Fisik dan Beban Kerja Melalui Stres Kerja - Dhelina Auza Utami; Kusuma Candra Kirana; Gendro Wiyono (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2020)
The purpose of this research is to determine the most influential and important variables that cause the low quality of employee performance at BBTKLPP Yogyakarta in accordance with the problems that have been formulated. A sample size of 90 that can represent the population is determined using the Krejcie-Morgan method. The method of analysis in this study is to use a variance-based analysis of Structural Equation Modeling (SEM), namely Partial Least Square (PLS). The sampling technique in this study is simple random sampling using a questionnaire instrument. Non-physical work environment variables have a positive but not significant effect on employee performance by showing p values of 0.581; Workload variable has a negative but not significant effect on employee performance with p values of 0.058; Non-physical work environment variables have a positive and significant effect on work stress and p values of 0.000; Workload variable has a positive and significant effect on work stress with an original sample value of 0.180 and a p value of 0.05; Work stress variables have a positive but not significant effect on employee performance as evidenced by the original sample value of 0.270 and p values of 0.327; Work stress as intervening influences the relationship between non-physical work environment variables and employee performance with tcount (9.26)> ttable (1.96); Work stress as an intervening effect on the relationship between workload variables and employee performance with a tcount (8.33)> ttable (1.96).